The Role of Communication on Motivation on Employee Performance Apartemen the Royal Olive Residence - Aprilia; Shofura Afifah; Amun; Eka Kurniawan; Geofakta Razali (Formosa Journal of Sustainable Research, 2023)
The company applies motivation to its employees with the aim of encouraging its employees to be productive. The company implements the motivation to get maximum performance from employees for the production section, there are demands from the company to be able to produce good quality for its production results. There are two methods used by PT Artistika Kreasi Mandiri, the direct method, where employees feel what they get directly, and the indirect method, such as facilities that can be felt, such as comfort at work, proven to motivate employees. From the observation results that the application of motivation applied by PT Artistika Kreasi Mandiri to its employees when viewed from Herzberg's two factor theory is in accordance with the theory but for the hygienic factor, namely salary according to the results of the salary questionnaire besides being a hygienic factor it can be a motivational factor because it can motivate employees in the production department